KONTRIBUSI KONSEP TAKWIL ULAMA USHULIYYUN DALAM PEWARISAN BEDA AGAMA - Ni'mah Siti Zuhrotun Ni'mah; Tutik Hamidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2021)
This paper discusses the contribution of the conception of takwil (interpretation) of the Ushuliyyun (theologians) in the concept of inheritance of various religions. The theologians derived the takwil method in the Istibath Ahkam as one of the methodologies of Islamic law. Takwil is a transfer from the foreign meaning to the concealed meaning based on the relevant arguments. This study applies library research as an approach by conducting studies on numerous legal materials considering the concept of takwil in inheritance of various religions. This study contributes comprehensive interpretation view concerning the dubs and educates that must be recognized so that the takwil carried out turns into accepted interpretation. As for takwil which bears no evidence and particularly due to the lust, this interpretation view could not be applied. The purpose of this interpretation approach that dealing with troubles in community concerning Islamic rule could be observed on the takwil application for inheritance in the different religions that are described so as to present the contemporary idea that the inheritance prohibition for different religions is particularly for the harby infidels. A Muslim also can be the heir of the non-Muslim infidels.